The role of MHD in 3D aspects of massive gas injection. (26th June 2015) - Izzo, V.A.; Parks, P.B.; Eidietis, N.W.; Shiraki, D.; Hollmann, E.M.; Commaux, N.; Granetz, R.S.; Humphreys, D.A.; Lasnier, C.J.; Moyer, R.A.; Paz-Soldan, C.; Raman, R.; et al.
Abstract: Simulations of massive gas injection for disruption mitigation in DIII-D are carried out to compare the toroidal peaking of radiated power for the cases of one and two gas jets. The radiation toroidal peaking factor (TPF) results from a combination of the distribution of impurities and the distribution of heat flux associated with the mode. When ignoring the effects of strong uni-directional neutral beam injection and rotation present in the experiment, the injected impurities are found to spread helically along field lines preferentially toward the high-field-side, which is explained in terms of a nozzle equation. Therefore when considering the plasma rest frame, reversing the current direction also reverses the toroidal direction of impurity spreading. During the pre-thermal quench phase of the disruption, the toroidal peaking of radiated power is reduced in a straightforward manner by increasing from one to two gas jets. However, during the thermal quench phase, reduction in the TPF is achieved only for a particular arrangement of the two gas valves with respect to the field line pitch. In particular, the relationship between the two valve locations and the 1/1 mode phase is critical, where gas valve spacing that is coherent with 1/1 symmetry effectively reduces TPF.